Defining “success” in large-scale agricultural investment: a typology based on different stakeholder perspectives - Logan Cochrane; Amr ElAlfy; Hossein Azadi; Melisew Dejene (Discover Sustainability, 2024)
Abstract In 2007/2008, a triple crisis of food, fuel and finance sparked a global rush for agricultural land; tens of millions of hectares were acquired, primarily by foreign investors, within countries in the Global South. Amidst those transactions, intergovernmental organizations, national governments, investors, and community members envisioned what “success” of such investments entails. Although not explicitly defined, each stakeholder had different conceptualizations and measures of it, based upon the descriptions used and desired outcomes sought. Despite a large amount of literature analyzing the global rush for land, as far as we are aware no one has analyzed the diverse viewpoints about what success entails. This paper compares conceptualizations among four key stakeholder groups, based on ideal types from dominant narratives, and develops a typology of ideal stakeholder framing of success to allow comparisons of uses and thereby provide a foundation for researchers who are assessing the global land rush. This paper provides clarity about widely used, but inconsistently defined, framing providing an important foundation for clarity of meaning and comparative differences between stakeholders. The typology advances the discourse on the land rush by providing nuance to this widely used framing and makes explicit its diverse meanings.